An international study of creative pedagogies in practice in secondary schools: Toward a creative ecology. Issue 2 (4th May 2018) - Harris, Anne; de Bruin, Leon
ABSTRACT: Schools' administrators and teachers feel the necessity to apply creative education within their learning environments, despite grappling with understandings of what creativity is and how best teachers can foster it in their students. This qualitative international study spanning the USA, Canada, Singapore, and Australia investigates teachers' perceptions regarding creative pedagogies that enhance creativity. Analyzing teachers' reflections on classroom pedagogy and school practice, this study explores ways teachers nurture critical thinking that foster creative intelligences. This study identifies pedagogical practices involving dialogic scaffolding, inter-disciplinarity, and creative environments and school practices that promote learning and thinking "out-side the box" in secondary school learners. This article posits a creativity index through which schools can gauge and assess attributes to nurturing creativity.